Sources of Finance, Innovation and Exportability in Asia: Cross-country Evidences. Issue 1 (April 2019) - Singh, Prakash; Maiti, Dibyendu
Abstract: Sunk costs determine the level of productivity and exportability of a firm according to the modern trade theory. While productivity rise requires finance for innovation and technology adoption from external sources, this article attempts to argue that sources of finance would be detrimental to the innovation ability of firms. Although formal banking finance suffers from asymmetric information, it is less risky to invest on R&D compared to that of non-banking sources and capital market. In other words, the fund received from formal banking source raises innovation, and, thereby, exportability of firms and financing from other sources involve higher cost and limit innovation capacity and exportability. Analysis of firm-level database provided by the World Bank Enterprise Survey confirms that firms depend more on formal banking source for investment in innovation, and this is found to be significant in explaining innovation and exportability. JEL Codes: F20, F36